Pengaruh Penerapan Green Accounting dan Environmental Performance terhadap Return on Asset - Titin Agustin Nengsih; M Nazori Majid; Pahlevi Ade Reza (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine the effect of the application of green accounting and environmental performance on Return On Asset. This research used a quantitative and the data analysis is multiple linear regression analysis. The sample used in this study were 6 companies in the Basic and Chemical Industry sector for 5 years with a total of 30 data. The results of this study indicate that the green accounting variable has a significant positive effect on Return On Asset and the environmental performance variable has no effect on the Return On Asset of companies in the Basic and Chemical Industry sector for the period 2016 to 2020. Meanwhile, the green accounting and environmental performance variables have an effect together. positive is not significant on the Return On Asset variable.